2007
DOI: 10.1108/09578230710762418
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and moral literacy in intercultural schools

Abstract: Purpose -The purpose of this paper is to explore what developing moral literacy for leaders in intercultural schools will mean. Design/methodology/approach -Relevant literature on moral literacy, leadership, intercultural schools and social learning is brought together and integrated to develop an understanding of the intricacies of leading for moral literacy. Findings -The foundation for developing moral literacy in intercultural schools requires leaders to become knowledgeable, cultivate moral virtues and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In summary, leadership is centrally concerned with the interpretation and enactment of values (Walker, Qian, and Chen 2007c). We know that leaders make a difference in schools.…”
Section: School Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, leadership is centrally concerned with the interpretation and enactment of values (Walker, Qian, and Chen 2007c). We know that leaders make a difference in schools.…”
Section: School Leadershipmentioning
confidence: 99%
“…For many potential leaders the prospect of becoming a principal is a confronting proposition (Walker and Kwan 2008). Policy-makers thus view leader development as vital to successful leadership (Walker, Qian, and Chen 2007c). As Pont, Nusche, and Moorman (2008) point out: 'There is widespread consensus among practitioners, researchers and policy makers that professional training and development have an impact on participants by improving leaders' knowledge, skills and dispositions ' (110).…”
mentioning
confidence: 98%
“…Deaux (1992) indicates that personal identity does not exist separately but on the basis of seeking the similarities with others. Moral leaders emphasize responsibility (Walker et al, 2007), exemplify for subordinates the distinction between rightness and wrongness of actions (Fairholm and Fairholm, 2009), and indicate ethical competence and moral courage (Haraway and Kunselman, 2006)—all of which are likely to influence subordinates through moral involvement (Etzoni, 1961), and thus evoke subordinates’ self-concept in the recognition that they share similar values with the leaders, or change subordinates’ self-concept so that their values become similar to that of the leaders (Pratt, 1998). Therefore, we argue that moral leadership is likely to enhance taking responsibility and thus promote the self-definition by subordinates as being responsible.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Also, virtue as an exploratory research construct is well grounded in the domain of leadership studies through the streams of morality, ethicality, spirituality, and transformation (Brown and Trevino 2006;Walker et al 2007;De Hoogh and Den Hartog 2008;Fairholm and Fairholm 2009;Zhang and Ng 2009;Yukl 2010). The present study was highly influenced by the six cardinal leadership virtues identified by Hackett and Wang (2012) rooted in virtue ethics in the realm of the Western and Eastern moral philosophies.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the Confucian doctrine held that cardinal virtues form the basis for all other virtues (Huang 1997). Through the relevant review of literature (Sarros and Santora 2001;Tuana 2003;Walker et al 2007); Hackett and Wang (2012) established that all these six cardinal leader virtues were culturally universal. Moreover, all these six cardinal leader virtues are characterized by interactivity and interconnectivity in terms of demonstrative behavioural responses evoked by the situation (Hackett and Wang 2012).…”
Section: Construct Developmentmentioning
confidence: 97%